Transcatheter Occlusion of Patent Ductus Arteriosus: Success Rate and Complications 5 Years Experience: Single Center in Isfahan - Ahmadi, Alireza; Sabri, Mohammadreza; Hashemi, Mohammad; gharipour, Mojgan (Acta Biomedica Atenei Parmensis, 2014)
Background and aim: Percutaneous occlusion of patent ductus arteriosus (PDA) has become increasingly attractive with the evolution of devices and techniques. This study aimed to report the total experience of a novel arterial occlusion device (Duct Occlude pfm) and Amplatzer. Methods: A descriptive study which selected non-randomized pediatric patients with patent ductus arteriosus (PDA) was performed between May 2007 to February 2012 on 99 children aged 8 months to 16 years who underwent attempted closure of PDA. Transcatheter occlusion was attempted in all the cases of coil through a 4-5 F and for Amplatzer 6-7 F delivery catheter. Findings: Devices were successfully deployed in 98% of patients. Amplatzer was used for thirty four patients (34%) due to medium to large PDA and coil was selected for sixty five patients (66%) due to small to medium size PDA.One day after the procedure, complete occlusion was accomplished in 42 (69%) out of 61 patients in whom the detachable coil device had been used on color-flow Doppler echocardiography. Embolization of a coil occurred on 1 occasion. Conclusion: Methods of detachable coil and Amplatzer type occlusion system compares favorably with other methods of transcatheter PDA occlusion.